Cholesterol embolization syndrome: report of two cases - Nazlı Dizman; Kübra Aydın Bahat; Şeyma Özkanlı; Abdullah Özkök (KARE Publishing, 2016)
Cholesterol embolization syndrome (CES) is a multi-systemic disease with immunological features which is a rare but an important cause of acute kidney injury (AKI) after invasive angiography. It frequently occurs in elderly male population with extensive atherosclerosis. CES should be considered in the differential diagnosis of AKI after angiography because its prognosis and treatment is completely different from contrast-induced nephropathy. Herein, we describe two cases of CES developed after invasive angiography. In the first case, renal biopsy was performed and CES was proved with characteristic renal lesions. The second patient had blue toe syndrome and persistent renal dysfunction.